Optimization Of Heterogeneous Fenton And Photo Fenton Reactions For The Treatment Of Palm Oil Mill Effluent Using Response Surface Methodology - Sani, Sadiq (2022)
Disposal of untreated palm oil mill effluent (POME) has adverse effects on aquatic biota and the environment due to its high chemical oxygen demand (COD) and total organic carbon (TOC) content. This work investigated the effectiveness of magnetite nanoparticles (Fe3O4 NPs) and carbon-encapsulated magnetite nanocomposites (Fe3O4@C NCs) as heterogeneous Fenton and photo-Fenton catalysts for POME treatment. Solvothermal and hydrothermal methods were employed to synthesise the two catalysts. The catalysts were characterised using various techniques and the optimisation of the experimental parameters were investigated via a one-step screening using a Box-Behnken design via response surface methodology involving seven variables which are catalyst dosage, H2O2 concentration, contact/irradiation time, dilution ratio, pH of POME, agitation speed, and absorption time. Four response variables: TOC reduction (TOCr), TOC reduction efficiency (ETOC), COD reduction (CODr) and COD reduction efficiency (ECOD) were evaluated and a total of 62 runs were considered. The models developed were refined, tested by analysis of variance (ANOVA) and validated using experimental data. The catalyst recyclability, kinetics and thermodynamics of POME removal were investigated.